(untitled) (Journal Of Educational and Psychological Researches, 2022)
The research seeks to design a program of guidance in the form of emotional perception rational to reduce the fear of failure, to identify the effect of method of emotional perception rational in reducing the fear of failure. To achieve these objectives, the researcher adopted the null-hypotheses, which assume there are no statistically significant differences in the degree of fear of failure (for the control group) in the pre-posttest. There are no statistically significant differences in the fear of failure (for the experimental group) in the pre-posttest. There were no statistically significant differences in the fear of failure of the groups (experimental and control) after the application of the program in the post-test. In order to test the hypotheses, the researcher used an experimental design with partial control (experimental group design and control group with pre-posttest). The sample consisted of (20) athletes and was randomized to two equal groups of a control group and an experimental group. The equivalence of the two groups was carried out in some variables (pre-test scores, age of months, the academic achievement of the father, academic achievement of the mother, and economic status). The method of emotional perception was applied to the experimental group while no method was provided for the control group. It constructed the measure of fear of failure, which has (26) paragraphs. The results showed that the application of the guiding method (rational emotional perception) had an effect in reducing the fear of failure. In light of the results of the research, the researcher put forward a number of recommendations and suggestions.